Activity coefficients at infinite dilution via a perturbation method of NRHB model. (23rd November 2022) - Baldanza, A.; Scherillo, G.; Mensitieri, G.; Panayiotou, C.
Highlights: Expressions for activity coefficients at infinite dilution of mixtures of low molecular weight fluids. Analytical expressions are obtained via perturbation of Non-Random Hydrogen Bonding EoS model. The approach accounts for specific intermolecular and intramolecular interactions. Abstract: Activity coefficients of solutes at infinite dilution play a central role in molecular thermodynamics of phase equilibria, solvation, solubility and related properties. Numerous equation-of-state models highly appropriate for concentrated systems have been developed in the open literature. Quite often, however, their equations for the chemical potential or the activity coefficient are not analytical and recursive numerical methods are needed for their use. This is the case for the versatile and widely used Non-Randomness with Hydrogen-Bonding equation of state model and, in the present work, a straightforward perturbation method is used for the derivation of analytical expressions for the chemical potential or the activity coefficient of solute at infinite dilution. The derivations are validated and compared with the full numerical calculations as well as with relevant experimental data. It is shown that calculations with the approximate analytical equations are essentially identical with the full numerical ones. These derivations are of a general character and may be used in a variety of other analogous thermodynamic models.